Does smoking have an impact on the immunological response to COVID-19 vaccines? Evidence from the VASCO study and need for further studies. (February 2022) - Ferrara, P.; Ponticelli, D.; Agüero, F.; Caci, G.; Vitale, A.; Borrelli, M.; Schiavone, B.; Antonazzo, I.C.; Mantovani, L.G.; Tomaselli, V.; Polosa, R.
Abstract: Objectives: The aim of this study was to investigate the possible impact of smoking on the humoral response to the BNT162b2 mRNA COVID-19 vaccine (also known as the BioNTech-Pfizer COVID-19 vaccine). Study design: A longitudinal sero-epidemiological study was conducted in sample of Italian healthcare workers (HCWs). Methods: HCWs who were administered two doses of the BNT162b2 mRNA vaccine, 21 days apart, between December 2020 and January 2021, were invited to undergo multiple serology tests to identify SARS-CoV-2 S-RBD-specific immunoglobulin G (IgG) antibodies. Participants also responded to questions about their smoking status (i.e. current smokers vs non-smokers) in a survey. Results: Sixty days after the completion of the vaccination cycle, serological analyses showed a difference in vaccine-induced IgG titre between current smokers and non-smokers, with median antibody titres of 211.80 AU/mL (interquartile range [IQR] 149.80–465.50) and 487.50 AU/mL (IQR 308.45–791.65) [ P -value = 0.002], respectively. This significant difference in vaccine-induced IgG titres between current smokers and non-smokers remained after adjusting for age, sex, and previous infection with SARS-CoV-2. Conclusions: This study observed that vaccine-induced antibody titres decrease faster among current smokers than non-smokers. Further research to investigate the impact of smoking on the immunological response to COVID-19 and non-COVID-19 vaccines is required.